Training of biology teachers: a look at the National Pedagogic University - Serrato, Deysi Liseth (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article arises from the initial developments of a research thesis for the Interinstitutional Doctorate in Education at the National Pedagogic University. The aim is to determine the historical conditions that have made possible the training of biology teachers at this university and the transformations in the curricula. To this end, an archaeological-genealogical perspective is adopted, based on concepts such as knowledge and power. There is an archive of more than 500 documentary sources, subject to processes of theming, hypertextual reading and identification of regularities. The findings show that the training of biology teachers in Colombia is crossed by expressions such as development, modernization, research, scientific training, among others. The early curricula have a biological disciplinary approach, while the pedagogical and educational components are addressed to a lesser extent. This contrasts with the more recent curricula, which allude to the teaching of biology and to the alive-life relation.